2018
DOI: 10.1002/uog.17564
|View full text |Cite
|
Sign up to set email alerts
|

De‐novo abnormal uteroplacental circulation in third trimester: pregnancy outcome and pathological implications

Abstract: Worsening of UtA Doppler is associated with HDP, independent of the value recorded in the second trimester. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
(56 reference statements)
1
16
0
Order By: Relevance
“…Our finding that abnormal first‐trimester uterine artery Doppler indices are invariably associated with defects in trophoblast oxygenation, cellular damage and function irrespective of pregnancy outcome, supports this hypothesis. Furthermore, we would like to point out that, in most cases of late‐onset pre‐eclampsia, mid‐trimester uterine artery Doppler indices are normal, becoming abnormal only in late pregnancy, just prior to development of pre‐eclampsia. Taken together, the findings of our studies and those of Orabona et al .…”
supporting
confidence: 88%
“…Our finding that abnormal first‐trimester uterine artery Doppler indices are invariably associated with defects in trophoblast oxygenation, cellular damage and function irrespective of pregnancy outcome, supports this hypothesis. Furthermore, we would like to point out that, in most cases of late‐onset pre‐eclampsia, mid‐trimester uterine artery Doppler indices are normal, becoming abnormal only in late pregnancy, just prior to development of pre‐eclampsia. Taken together, the findings of our studies and those of Orabona et al .…”
supporting
confidence: 88%
“…The subsequent fall in UtA‐PI with advancing gestation is thought to result from decreasing impedance to the uterine blood flow as trophoblast invasion is eventually completed. However, we, and others, have demonstrated that there is a de‐novo increase in third‐trimester UtA‐PI in pregnancies that are at increased risk of HDP. Furthermore, de‐novo increase in UtA‐PI in the third trimester is also associated with FGR, stillbirth and adverse clinical outcomes, even in the absence of HDP.…”
Section: Introductionmentioning
confidence: 70%
“…The fact that these differences can be observed in the third trimester of pregnancy, after completion of the spiral artery invasion, supports this theory. The previous finding of a de‐novo increase in UtA‐PI in the third trimester of HDP pregnancy is also better explained by differences in maternal cardiovascular function than by spiral artery invasion. Similar hemodynamic indices between term HDP and healthy pregnancy do not necessarily indicate that two different pathologies are responsible for preterm and term HDP.…”
Section: Discussionmentioning
confidence: 88%
“…32 Furthermore, the relatively frequent finding of de novo increase in third-trimester uterine artery resistance indices is unlikely to be related to changes in trophoblast invasion, because this would require a biologically implausible "deconversion" of the spiral arteries in the third trimester of pregnancy. 33 Doppler studies of other peripheral waveforms, such as in the ophthalmic and radial arteries, also Expert Review ajog.org demonstrated abnormal indices several months before the onset of PE. 34 Early pregnancy ophthalmic artery and radial artery Doppler evaluation is as effective as uterine artery Doppler assessment in screening for PE.…”
Section: Uteroplacental Hypoperfusion and Maternal Cardiovascular Functionmentioning
confidence: 98%